Role of cardiac troponin I in staging and prognosis of congestive heart failure subjects - Ahmed, N; Asad, K; Rahman, MM; Wahab, MA; Haque, MR; Mollah, FH; Arslan, MI (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):12-6. The abstract of this article is available on the PubMed website